Analisis Penggunaan Google Analytics dan Google Search Console untuk Meningkatkan Strategi Digital Marketing Website SEAL - Feri Fajar Febriansyah; Rr. Tri Istining Wardani; Tri Ramadani Arjo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
A website is a key digital asset organizations use to run Digital Marketing strategies, including SEAL, which uses seal.or.id as its information and marketing medium. The identified problem is the suboptimal use of website analytics data to support Digital Marketing strategy at the Awareness, Interest, and early Conversion stages of the Digital Marketing Funnel. This study aims to analyze the performance of the SEAL website using Google Analytics and Google Search Console, evaluate its effectiveness, and formulate data-driven Digital Marketing recommendations. The study used a quantitative approach with a descriptive-evaluative method. Primary data were collected from Google Analytics and Google Search Console metrics during February 1-May 1, 2026, complemented by limited on-page SEO optimization on four main pages. Results show that at the Awareness stage, organic search dominated with 980 sessions and 32,400 impressions at an average position of 6. At the Interest stage, the Homepage recorded 1,490 views and the Article page achieved the highest engagement rate at 88.14%. At the early Conversion stage, the Instagram link received the most clicks (112; 29.55%). After SEO optimization, impressions rose 67.8%, clicks rose 37.4%, users rose 78.04%, and new users rose 83.65%. Google Analytics and Google Search Console proved effective as data-driven tools for formulating SEAL's sustainable Digital Marketing strategy.